SISTEM INFORMASI PENGELOLAAN DATA ALUMNI BERBASIS WEB PADA SMK BINA MANDIRI 2 SUKABUMI - Rana Dewi; Jeni Sundari (Department of Information Technology, Universitas Timor, Indonesia, 2021)
Schools must have alumni information data after graduating from school, so far the data collection is only done by taking notes in printed documents, resulting in data management that cannot be done quickly and still often has errors and is difficult to update, this problem can be overcome with a the method that is developing is the programming system. One of them is programming in the form of software. With this information management system software, it is expected to help manage school alumni data.